Fermentative production of hydrogen in presence of modified mesoporous silica SBA-15. (9th November 2016) - Seifert, K.; Dyba, K.; Góra-Marek, K.; Stodolny, M.; Zagrodnik, R.; Łaniecki, M.
Abstract: Hydrogen production was studied in the series of batch tests at 310 K in the presence of digested sludge free from methanogenic bacteria, glucose as the source of organic carbon and mesoporous silica of SBA-15 type as the adhesion-like material. Although mesopores of SBA-15 are too small for accommodation of bacteria (in this study mainly Clostridium and Enterobacter ) within the porous system of SBA-15, the obtained results showed that process efficiency and reaction rate were significantly improved in presence of modified SBA-15 in comparison with those results obtained in their absence. The amount of produced hydrogen in presence of small amounts of non-modified and surface modified (NH2, Al 3+ ) SBA-15 was apparently higher of about 50% (20% for non-modified SBA-15) than in suspensions without silica. Experiments with SBA-15 modified with SO3 H groups showed negative influence of acidic surface properties on hydrogen production. Appropriate surface properties (mainly basic) of silica are probably responsible for better adhesion and propagation of bacteria properties, biofilm formation and in consequence higher activity. Moreover, systems containing SBA-15 are more resistant to temperature changes of medium. Sequential adjustment of reaction pH with stabilization at 5.5 improved the efficiency of hydrogen production. Highlights: Activity of immobilized (SBA-15 silica) fermentative bacteria in biohydrogen production. Influence of surface acidic and basic properties of SBA-15 on activity. Immobilization of bacteria on basic surfaces increase and stabilize activity. Mesoporous structure of SBA-15 do not play any essential role in hydrogen production via dark fermentation.